Local mesh refinement for incompressible fluid flow with/without free surfaces - Terasaka, Haruo; Kajiwara, Hikaru; Tanaka, Nobuatsu (Computer Assisted Methods in Engineering and Science, 2023)
This paper presents a local mesh refinement (LMR) technique and its application to incompressible fluid flows with or without free surface boundaries. In the LMR method patches of fine grid are embedded in arbitrary regions of interest. Hence, more accurate solutions can be obtained with a lower number of computational cells. LMR is very suitable for the simulation of free surface movements because free Surface flow problems generally require a finer computational grid to obtain adequate results. By means of this technique one can place finer grids only near surfaces and thus greatly reduce the total number of cells and computational costs. This paper introduces two LMR codes. Numerical examples calculated with the codes demonstrate well the advantages of the LMR method.